An Integrated Model of Market and Limit Orders - Chakravarty, Sugato; Holden, Craig W. (Journal of Financial Intermediation, 1995)
We develop an integrated model in which a risk-neutral informed trader optimally chooses any combination of a market buy, a market sell, a limit buy including the limit buy price, and a limit sell including the limit sell price. Limit orders undercut the market maker and generate transactions inside the bid-ask spread. The informed trader exploits limit orders by submitting market orders even when the terminal value is inside the spread. When the terminal value is above the bid, a combined market buy-limit sell is more profitable than a market buy only. We obtain an analytic solution. Journal of Economic Literature Classification Numbers: D40, D82, G12, G14.